Comparison of Correlation Between Cut Weight and Giblet Organ Weight in Broiler Chickens Given and Not Given White Turmeric Juice - Horhoruw, Wiesje Martha (Journal of Comprehensive Science, 2025)
Global broiler production has reached 131.4 million tons in 2023, with Indonesia contributing 3.8 million tons, making optimization of live weight crucial for meeting growing protein demands. Traditional growth promoters face increasing restrictions due to antibiotic resistance concerns, driving the need for natural alternatives. The aim was to find out the correlation between live weight and giblet organ weight in broiler chickens that were given and not given white turmeric juice. This research was divided into 2 treatments, namely treatment A = without white turmeric juice treatment, and Treatment B = 40 ml of white turmeric juice and 960 ml of water (4% white turmeric juice). The parameters measured were cut weight, liver weight, heart and gizzard. To determine the relationship between the weight of the cut and the weight of giblet organs (liver, heart and gizzard) in broiler chickens that were given and not given white turmeric juice was analyzed by correlation analysis. The results showed that the correlation between the weight of the cut and the weight of the giblet organ in broiler chickens fed and not given 4% white turmeric juice tended to be the same. The comparison of the correlation values between cut weight and liver weight was 0.539 and 0.413 with a moderate relationship; The comparison of the correlation values between cut weight and heart weight was 0.540 and 0.572 with a moderate relationship; and The comparison of the correlation value between the cutting weight and the weight of the gizzard h was 0.369 and 0.331 with a low relationship level. These findings provide valuable insights for poultry nutritionists and farmers seeking natural feed additives to optimize broiler performance while maintaining organ development proportionality, contributing to sustainable and chemical-free poultry production systems.